Direktori Hasil Akreditasi Program Studi Tahun 2004, Buku II Perguruan Tinggi Swasta - [Tidak Terdaftar] (Depdiknas BAN PT, 2004)
Direktori Hasil Akreditasi Program Studi Tahun 2004, Buku II Perguruan Tinggi Swast